Race becomes tomorrow : North Carolina and the shadow of civil rights - Sider, Gerald M. (Duke University Press, 2015)
Gerald M. Sider weaves together stories from his civil rights activism, his childhood, and his experiences as an anthropologist to investigate the dynamic ways race has been constructed and lived in America since the 1960s.